KONSEP DASAR MANAJEMEN DAN BISNIS SYARIAH STUDI KASUS PERKEBUNAN DAN INDUSTRI KELAPA SAWIT DI KABUPATEN SAMBAS - Munawir (Cross-Border Journal of Business Management, 2026)
This study aims to analyze the fundamental concepts of Islamic management and business and their relevance in modern economic practices. Islamic management and business constitute a business management system that is not only profit-oriented but also grounded in spiritual values and Islamic ethics. This study employs a library research method using a descriptive- analytical approach through a review of literature from books and scholarly journals on Islamic economics. The findings indicate that the fundamental concept of Islamic management is based on the principles of tawhid (monotheism), amanah (trustworthiness), justice (‘adl), and maslahah (public benefit). Meanwhile, Islamic business rejects practices involving riba (usury), gharar (uncertainty), and maysir (gambling), and emphasizes transparency, honesty, and social responsibility. The implementation of these concepts is reflected in the development of Islamic financial institutions, Islamic cooperatives, and the halal industry in Indonesia. This study concludes that Islamic management and business offer a business management model oriented toward balancing economic efficiency and spiritual blessing, thereby holding the potential to realize a more just and sustainable economic system.